Fermion localization on branes with generalized dynamics - Castro, L. B.; Arroyo Meza, L. E. [UNESP] (IOP Publishing, 2013)
In this letter we consider a specific model of braneworld with nonstandard dynamics diffused in the literature, specifically we focus our attention on the matter energy density, the energy of system, the Ricci scalar and the thin-brane limit. As the model is classically stable and capable of localize gravity, as a natural extension we address the issue of fermion localization of fermions on a thick brane constructed out from one scalar field with nonstandard kinetic terms coupled with gravity. The contribution of the nonstandard kinetic terms to the problem of fermion localization is analyzed. It is found that the simplest Yukawa coupling η ωφ ω supports the localization of fermions on the thick brane. It is shown that the zero mode for left-handed fermions can be localized on the thick brane depending on the values for the coupling constant η. Copyright © EPLA, 2013.